Evaluation of three different remineralizing agents on artificially demineralized enamel lesions: Using scanning electron microscopy-energy dispersive X-ray and magic-angle spinning nuclear magnetic resonance - An in vitro study - Divya Vijay Mehta; Shakuntala B Siddaiah (Wolters Kluwer Medknow Publications, 2022)
Aim: Demineralization can be arrested or reversed when remineralization agents are applied to incipient carious or noncavitated carious lesions. A large number of therapeutic agents, including nonfluoridated products, have been developed to promote enamel remineralization. This study aims to evaluate the efficacy of different remineralizing agents on artificially demineralized enamel lesions. Materials and Methods: The present in vitro study was conducted on 75 sound premolars divided into three groups of normal, demineralized (n = 15 each), and remineralized teeth (n = 45). The remineralized teeth were further subdivided into three groups (n = 15) as remineralized with 2% sodium fluoride (NaF), 2% NaF, and Psoralea corylifolia (bakuchi) and white mineral trioxide aggregate. Specimens of each group were treated with the above-mentioned remineralizing agents and then subjected to Vickers hardness number (VHN), scanning electron microscopy-energy dispersive X-ray (SEM-EDX), and magic-angle spinning nuclear magnetic resonance (MAS-NMR) for further evaluation. Results: The test results showed significantly the highest VHN and the emission peak of elements under the EDX test, such as calcium, phosphorous, oxygen, and fluorine with remineralized with NaF + bakuchi. MAS-NMR spectra showed fluorine and phosphorous peak in a group with NaF + bakuchi indicative of the increase in remineralization. NaF + bakuchi showed effective results in VHN, SEM-EDX, and MAS-NMR with no antagonist interaction. Conclusion: Thus, P. Corylifolia presents an advantage in enhancing remineralization and inhibiting demineralization for early carious lesions and can be used as a herbal extract for effective reduction in pathogenic bacteria.